LARVICIDAL POTENTIAL OF SOME INDIAN MEDICINAL PLANT EXTRACTS AGAINST AEDES AEGYPTI (L.) - SHIVAKUMAR, M. S.; SRINIVASAN, R.; NATARAJAN, D. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The larvicidal potential of different solvent crude (hexane, chloroform, ethyl acetate, acetone and methanol) leaf extracts of four plants (Blepharis maderaspatensis, Elaeagnus indica, Maesa indica, Phyllanthus wightianus and Memecylon edule) was tested against the fourth-instar larvae of Aedes aegypti. Insecticidal susceptibility tests were carried out using WHO standard method and the mortality was observed after 24-h exposure. All the tested extracts showed moderate to good larvicidal activities. However, the maximum larval mortality was detected in acetone extract of E. indica (LC50 90.89, LC90 217.21 and LC99 441.88 ppm) followed by M. indica acetone extract (LC50 173.21, LC90 289.86 and LC99 441.04 ppm). These results revealed that larvicidal properties of the selected plants and encourages further effort to investigate the bioactive compounds in those extracts that might possess good larvicidal properties when it will be isolated in pure form. Keywords: Blepharis maderaspatensis, Elaeagnus indica, Maesa indica, Phyllanthus wightianus, Memecylon edule, dengue vector mosquito.